TEACHERS’ PERSPECTIVES OF TEACHING ENGLISH TO YOUNG LEARNERS (A DESCRIPTIVE STUDY AT PRIMARY SCHOOLS IN KUDUS) - Sri Endang Kusmaryati (Universitas Negeri Makassar, 2020)
ABSTRACTIn Indonesia teaching English at primary schools aims to introduce English language as a foreign language. The policy of Departemen Pendidikan Nasional, No.0487/14/1992, Chapter VIII and Undang-undang Sistem Pendidikan Nasional, No.060/U/1993 explains that English can be incorporated into the curriculum of local content at primary schools. The English proficiency of primary school graduates should be appopriate and useful to prepare the to learn English at the higher level. Students of primary schools are young learners who have their own characteristics. Young learners take great pleasure in playing games. Therefore, teaching English for primary schools students must be well designed in accordance with the characteristics of the students. This study is a survey that aims to investigate teachers’ perspectives of teaching English to young learners in Kudus. Further, it inspects their problems in teaching English in their schools. A questionnaire is distributed to the targeting primary school teachers in Kudus. The result reveals that there are 67% of the teachers who agreed that English is appropriately taught at primary schools, while 33% of the teachers disagreed. Teachers’ problems in teaching English to primary schools students, among others are the limited time allotments, students’ proficiencies in vocabulary and pronunciation, students’ interests, limited facilities, textbook, media and learning materials, and too many students in the classroom. Besides, the primary school students are young learners who are very active and like to break the rules.